A hybrid approach for water resources management in Tunisia. (2019) - Elleuch, Mohamed Ali; Elleuch, Lobna; Frikha, Ahmed
Optimal water resources management is often related to the desirability of achieving equitable distribution of water among the users based on economic, social, availability, reliability and environmental procedures. In Tunisia, the main issues of water resources management are addressed with specific reference to the available water resources and water demand from domestic, agricultural, tourism, municipal and industry sectors. Usually, there is increasing competition for water among the various water use sectors in several regions of Tunisia. Water policy and legal frameworks are some of the feasible measures that provide opportunities to evolve a systematic approach to water resources management. For that, this paper describes the development of a hybrid approach for the evaluation and allocation of potential water resources management for many sectors according to several criteria. A hybrid approach between the reciprocal weights method (RR) based on the results of the Delphi method, the analytic hierarchical process (AHP) and the Hurwicz criterion method (HCM) has been developed to evaluate and select the best water resources for Sfax (Tunisia) based on sensitivity analysis.